Comparison of changes in rice morphoagronomy and physiology based on decrease in soil water potential - Cut Nur Ichsan; Rifa Azkia Halva; Gina Erida; Trisda Kurniawan; Erita Hayati; Erida Nurahmi; Ainun Marliah; Mardhiah Hayati; Juliawati (Faculty of Agriculture, Universitas Malikussaleh, 2026)
This study aims to analyze changes in the morphological, agronomic, and physiological characteristics of rice plants in response to a decrease in soil water potential. The study was conducted through a literature review of various relevant and credible scientific journals. The results indicate that a decrease in soil water potential (kPa) is closely associated with the level of drought stress affecting rice growth and productivity. Water stress reduces plant height, the number of tillers, and leaf area index (LAI), and increases leaf rolling as an adaptive mechanism. Physiologically, there is a decrease in relative water content (RWC), impaired photosynthesis, increased spikelet sterility, and reduced grain filling. These impacts become more significant during the reproductive phase. Therefore, water management based on soil water potential thresholds is crucial for maintaining sustainable rice productivity.